The value of interleukin-27 for differentiating tuberculous pleural effusion from Mycoplasma pneumoniae pneumonic effusion in children - Xu, Hui; Yang, Haiming; Liu, Jinrong; Liu, Hui; Tang, Xiaolei; Li, Huimin; Cai, Siyu; Zhao, Shunying (Frontiers in Pediatrics, 2022)
Objectives: The early diagnosis of tuberculous pleural effusion (TPE) is challenging due to the difficulty of isolating of Mycobacterium tuberculosis and pleural biomarkers are an option choice. Recent studies showed that interleukin-27(IL-27) appear to be a new accurate biomarker for TPE in adults and no related studies were reported in children. In this study, we aim to evaluate the potential value of IL-27 in pediatric tuberculous pleurisy by detecting its levels in pleural fluid and serum. Methods: Forty-eight children with tuberculous pleural effusion and sixty-four with severe Mycoplasma pneumoniae pneumonic effusion (SMPPE) were enrolled in this study. IL-27 concentrations were measured in serum and pleural fluid. The diagnostic yield of IL-27 was evaluated using receiver operating characteristic curves. Results: The level of p-IL-27 in TPE showed statistically no significant difference when compared with SMPPE (p>0.05). However, the ratios of pleural fluid IL-27/serum IL-27 (p-IL-27/s-IL-27) in TPE were significantly much higher than those in SMPPE (p<0.05). By analysis of the ROC curves, the diagnostic sensitivity and specificity of p-IL-27/s-IL-27 ratio were 100% and 48.44% respectively (cut-off value of 1.0280). The area under the receiver operator characteristic curve for p-IL-27/s-IL-27 were 0.7295. Conclusions: Pleural fluid IL-27 alone was not accurate in in distinguishing pediatric TPE from SMPPE, which was different from the diagnostic value of IL-27 in adult studies due to the different disease spectrum between children and adults. Our results implied that the p-IL-27/s-IL-27 ratio had potential value in distinguishing TPE from SMPPE. However, the specificity of IL-27 was relatively lower and it is necessary to find a more specific marker in tuberculous pleurisy of children.